Antioxidative effect of schisanhenol on human low density lipoprotein and its quantum chemical calculation - YU Ling-hong; LIU Geng-tao; SUN You-min; ZHANG Hong-yu (Acta Pharmacologica Sinica, 2016)
AIM: To investigate the effect of schisanhenol (Sal) on copper ion-induced oxidative modulation of human low density lipoprotein (LDL). METHODS: The antioxidative activity of eight schisandrins (DCL) on microsome lipid peroxidation induced by Vit C/NADPH system was first observed, and then, the effect of Sal on Cu2+-induced human LDL oxidation was studied. The generation of malondialdehyde (MDA), lipofuscin, reactive oxygen species (ROS), consumption of a-tocopherol as well as electrophoretic mobility of LDL were determined as criteria of LDL oxidation. Finally, the quantum chemical method was used to calculate the theoretical parameters of eight DCL for elucidating the difference of their antioxidant ability. RESULTS: Sal was shown to be the most active one among eight schizandrins in inhibiting microsome lipid oxidation induced by Vit C/NADPH. Sal 100, 50, and 10 micromol/L inhibited production of MDA, lipofuscin and ROS as well as the consumption of a-tocopherol in Cu2+-induced oxidation of human LDL in a dose-dependent manner. Sal also reduced electrophoretic mobility of the oxidized human LDL. Further study of quantum chemistry found that Sal was the strongest one among eight DCL to scavenge O2, R, RO and ROO radicals. CONCLUSION: Sal has antioxidative effect on human LDL oxidation. The mechanism of Sal against LDL oxidation may be through scavenging free radicals.